The Study of James Rosenau's Affiliation Theory with an Emphasis on the Role of Individual and International System Variables in the Analysis of Regionalism in the Second Pahlavi and Islamic Republic of Iran - Hassanpour Dehnavi, Hossein (2021)
Different theoretical approaches can be used to analyze countries' foreign policy and regionalism. The present study intends to study and compare the policy of regionalism of Iran in the second Pahlavi era and the Islamic Republic based on the theoretical approach of James Rosenau, using the variables of decision-making personality, role, government, society and international system variables. Iran's regionalization policy during the Second Pahlavi period was in line with the structure of power in the international system. At the same time, Iran, in this period influenced by the structure of the bipolar system and the Cold War, also sought to gain supremacy and leadership in the region, as the most important person in foreign policy decision-making and in the personality of Mohammad Reza Shah. On this basis, we can say that the two variables of the international system and the decision-making personality were the most important variables influencing the process of foreign policy and regionalism of Iran during this period. In the Islamic Republic, with the formation of ideological elements such as the construction and nature of political power based on the velayat-e faqih and the idea of issuing a revolution, the policy of regionalism was in conflict with the structure of power in the international system and in line with ideological foundations and interests. Accordingly, the two variables of the international system and the decision-making personality were the most important variables influencing the process of foreign policy and regionalization of Iran during this period. The purpose of this paper is to use a descriptive-analytical method, a comparative study and to use the historical data to study the effect of each of these variables on the regionalization process.